Cork-polylactide composites reinforced with polyhydroxyalkanoates for additive manufacturing - Silva, Sara. P. Magalhães da (2020)
Cork-polymer composites (CPC) consisting of 85% wt of polymeric matrix and 15% wt. of cork powder residues were developed. The polymeric matrix was composed by PLA, PHA and different blends of PLA/PHA. Three different blend weight ratios of PLA/PHA were studied, namely 75:25, 50:50 and 25:75. CPC were prepared by melt compounding using a Brabender type mixer. Mechanical analyses, including tensile and impact tests, as well as morphological analyses through scanning electron microscopy, were performed. When compared to composite only prepared with PLA (CPC 1), the addition of PHA to PLA promotes more ductile composites. Through impact tests, it was also observed the toughening effect of PHA when added to PLA. The CPC prepared with the blend PLA:PHA=75:25 revealed to have better mechanical performance among the ones prepared with the other blend ratios. From morphological analyses, it was perceived the miscibility of both polymeric matrices.